2021
DOI: 10.1002/ps.6757
|View full text |Cite
|
Sign up to set email alerts
|

The effects of beta‐cypermethrin, chlorbenzuron, chlorothalonil, and pendimethalin onApis mellifera ligusticaandApis cerana ceranalarvae rearedin vitro

Abstract: BACKGROUND Declines in bee populations and diversity have drawn international attention. The long‐term use of chemical pesticides has affected bee behavior and physiology. This study aimed to investigate the effects of chronic exposure to four commonly used chemical pesticides (beta‐cypermethrin, chlorbenzuron, chlorothalonil and pendimethalin) on the growth of Apis mellifera ligustica and Apis cerana cerana larvae reared in vitro. RESULTS Pesticide type and concentration were the main factors affecting honeyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Residues of this herbicide were also detected in wax, pollen and bee samples from North America and Germany [85][86][87]. According to He et al [88], exposure to pendimethalin had no significant effect on the development of honeybee larvae; however, its detection in honeybees and hive products seems to pose a risk to honeybees. We also detected DDT derivatives (residues of p,p' DDT) in samples of dead honeybees.…”
Section: Discussionmentioning
confidence: 98%
“…Residues of this herbicide were also detected in wax, pollen and bee samples from North America and Germany [85][86][87]. According to He et al [88], exposure to pendimethalin had no significant effect on the development of honeybee larvae; however, its detection in honeybees and hive products seems to pose a risk to honeybees. We also detected DDT derivatives (residues of p,p' DDT) in samples of dead honeybees.…”
Section: Discussionmentioning
confidence: 98%
“…The impacts of pesticides on insect fitness have been extensively studied, and some pesticides reduced the fitness of bee larvae of both Apis mellifera and Apis cerana ( He et al, 2022 ). Even sublethal imidacloprid can affect foraging and colony fitness in Monomorium antarcticum and Linepithema humile ( Barbieri et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 , Tables 3 and 4 ), such as the root-knot nematodes exposed to recommended field doses of pendimethalin (3 µL cm −2 ) (Das et al 1998 ; Dopierala and Giebel 2002 ). In contrast, it had no significant effects on larval survival and pupation and eclosion rates of Apis mellifera ligustica and A. cerana cerana at doses of 7.0 ng g −1 and 15.5 ng g −1 (He et al 2022 ). Laboratory tests have shown that pendimethalin at field concentrations has no effect on soil invertebrates (Belden et al 2005 ), including larvae of the green lacewing Chrysoperla carnea (Maia et al 2016 ).…”
Section: Side Effects Of Chronic Exposurementioning
confidence: 99%